KEMAMPUAN MENYUSUN ALAT EVALUASI HASIL BELAJAR DITINJAU DARI DISIPLIN GURU DAN MOTIVASI BERPRESTASI PADA SMK SWASTA DI JAKARTA SELATAN - Rasam, Fadli (RESEARCH AND DEVELOPMENT JOURNAL OF EDUCATION, 2014)
This research aims to discover and analyze empirically ability to prepare an evaluation tool of learning outcomes in terms of teacher discipline and achievement motivation. Affordable population in this study was the teachers ofsocial studies in the schools wich amoun to N=135 and selected a random sampel n=30 teachers of social science. Research method used was a survey with correlation and regression analysis. Data obtained from the questionnaires to the respondents, the discipline teacher professional achievement motivation and theÂ ability to prepare an evaluation tool of learning outcomes. Results show there are significant teacher discipline and achievement motivation are together on the ability of crafting tools evaluation of learning outcomes in social sciences fields of study. This can be proved by calculating the value of f = 5.986 and sig. 0.007 <0.05. Then there is also a disciplinary effect on the ability of teachers (X1) prepare an evaluation tool and significant learning outcomes (Y) this can be proven with t count = 2.411 and sig. = 0.023 < 0.05. Furthermore, there is no significant effect of achievement motivation (X2) on the ability of crafting tools evaluation of learning outcomes (Y). This can be proved t = 1.577 and sig. = 0.126> 0.05.Key words: ability to prepare an evaluation tool of learning outcomes, teacherdiscipline, achievement motivation